FULL-SCALE LOAD TESTING OF STRUCTURES - A SIGNIFICANT STEP TO IMPROVING DEFORMATION SAFETY - Gusev, G.N.; Matveenko, V.P.; Tsvetkov, R.V.; Shardakov, I.N.; Shestakov, A.P. (Perm Federal Research Centre Journal, 2015)
The basic principles of development of an experimental stand for recording pre-critical and critical processes taking place in structures are considered. A model is developed to describe the specific features of the deformation behavior of a reinforced concrete structure at the initial stage of damage accumulation. Simulation results are obtained for elements of the reinforced concrete structure of half scale. Parameters of the experimental stand and operating conditions of loading devices are determined. The scheme of the experimental stand is presented.